BLACK-Red-Gold in "der bunten Republik" constructions and performances of Heimat/en in Post-Wende Afro-/Black German cultural productions - Plumly, Vanessa D. (University of Cincinnati, 2015)
While the Afro-/Black German population in the Federal Republic of Germany continues to seek national recognition, the volume and diversity of their cultural output has begun to receive its own international attention. This dissertation is an interdisciplinary study that assesses the multiplicity of the discursive constructions and performances of the imagined, yet real concept of Heimat in Black German cultural productions. These productions introduce a decolonization of the culturally and politically laden, as well as hegemonically and heteronormatively conceived, exclusionary space of (German) Heimat. In studying these re-imaginings and reconfigurations and the performative acts that constitute them in select Black German political and aesthetic works, I contend that Heimat is not only performed in resistance to a singularly imagined German origin and space of whiteness, but is also revealed to be a more vital construct than other forms of imagined communities. Black Germans, while rooted by their German cultural inheritance, simultaneously traverse the borders of the bounded German nation and interact on a global scale in the realm/s of the transnational Black diaspora. Heimat encompasses elements of both of these imagined communities; yet, it still can be distinguished from them. Persisting through contradictions, the plural Heimat/en of Black Germans become geographically situated, but also internalized (non- )spaces/places that are simultaneously individual and collective (corporeal in both senses of the 'body'), voluntary and involuntary, inclusive and exclusive, local, national, and transnational, and dangerous and safe
Lteraturverzeichnis Seite 284-320
Keywords: Geschichte; Heimat -- Motiv; Literatur; Kultur; Schwarze; Deutschland; Germanic literature; Black German; Afro- German; African Diaspora; German Heimat; Cultural anthropology; Political science; Film studies; African studies; Black studies; Academic theses; Hochschulschrift